Low first-year apparent survival of passerines in abandoned fields in northwestern Russia. (6th March 2020) - Shitikov, Dmitry; Grudinskaya, Viktoria; Makarova, Tatiana; Vaytina, Tatiana; Fedotova, Svetlana; Samsonov, Stanislav; Grabovsky, Alexander
Abstract: First-year survival probability of migratory passerines during the period between fledging and first reproduction is a highly variable parameter that has a major effect on population dynamics. We used a long-term mark–recapture dataset (2002–2018) to examine first-year survival of 3 passerine species breeding in abandoned agricultural fields of northwestern Russia: Booted Warbler ( Iduna caligata ), Whinchat ( Saxicola rubetra ), and Western Yellow Wagtail ( Motacilla flava ). We banded 3, 457 nestlings, including 1, 363 Booted Warblers, 1, 699 Whinchats, and 395 Western Yellow Wagtails, and resighted 12 Booted Warblers, 29 Whinchats, and 13 Western Yellow Wagtails in the year after fledging. We evaluated first-year apparent survival rates using Cormack-Jolly-Seber models in MARK program within the multispecies approach. We tested effect of fledge date on the first-year apparent survival. In all focal species, first-year apparent survival rates were low and reached the lower limits known for migratory passerines. We found no differences in first-year survival rates among the 3 species: the estimated average first-year apparent survival rate of all species was 0.05 ± 0.01. The fledge date had a considerable impact on first-year survival rate: later fledge dates negatively affected first-year survival. We suggest that first-year apparent survival rates in our study were low due to low natal philopatry and high mortality in the post-fledging period. Low apparent first-year survival may be a specific feature of open-nesting birds breeding in abandoned fields that are low-quality habitats because of high predation pressure.